2021
DOI: 10.1186/s13613-021-00880-y
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and stress among ICU healthcare professionals in France according to intensity of the COVID-19 epidemic

Abstract: Background We investigated the impact of the COVID-19 crisis on mental health of professionals working in the intensive care unit (ICU) according to the intensity of the epidemic in France. Methods This cross-sectional survey was conducted in 77 French hospitals from April 22 to May 13 2020. All ICU frontline healthcare workers were eligible. The primary endpoint was the mental health, assessed using the 12-item General Health Questionnaire. Source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
41
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 46 publications
1
41
0
2
Order By: Relevance
“…Furthermore, during the pandemic, nurses faced a disruption in their everyday activity, as they found themselves in the position of caring closely for patients suddenly deprived of their families, causing a significant emotional burden and a feeling of inadequacy. This situation inevitably led to an increase of psychological distress [43]. As described by Laurent et al [44], when dealing with end-of-life decisions, nurses tend to consider themselves as simple executing agents, in order to dissociate themselves from decisions in which they did not participate.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, during the pandemic, nurses faced a disruption in their everyday activity, as they found themselves in the position of caring closely for patients suddenly deprived of their families, causing a significant emotional burden and a feeling of inadequacy. This situation inevitably led to an increase of psychological distress [43]. As described by Laurent et al [44], when dealing with end-of-life decisions, nurses tend to consider themselves as simple executing agents, in order to dissociate themselves from decisions in which they did not participate.…”
Section: Discussionmentioning
confidence: 99%
“…The authors explained this by the fact that regular ICU staff had to both deal with the first wave of the pandemic and train the reinforcement, with greater responsibility for any potential errors committed by the support staff, thus profoundly disturbing the usual working conditions. Conversely, in the PsyCOVID-ICU study [5], involving 77 hospitals throughout France, our group previously showed that support staff redeployed to the ICU were at higher risk of psychological distress as compared to permanent ICU staff.…”
Section: Introductionmentioning
confidence: 87%
“…Numerous studies have investigated the impact of the COVID-19 pandemic on healthcare workers in units dedicated to the care of COVID-19 patients, reporting high levels of anxiety, depression, burnout, insomnia and psychological distress [5][6][7][8][9][10]. Among health professionals, meta-analyses reveal a frequency of 12.2-36% for depression and 13-37% for anxiety [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%